Perancangan Sistem Pengelolaan Dokumen menggunakan Prototype dan ISO 25010 pada PT Snapdev Digital Indonesia - Adinda Nurul Hikmah Alkautsar; Laila Khusnul Afifah; Chairul Anwar (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2026)
Document management is an essential activity in supporting the effectiveness and efficiency of business processes within an organization. PT Snapdev Digital Indonesia still experiences several challenges in document management, including unstructured document storage, difficulties in document retrieval, document duplication, and the absence of an integrated document version control system. This research aims to design and develop a web-based Document Management System using the Prototype method and evaluate its software quality based on the ISO/IEC 25010 standard. The Prototype method was selected because it enables continuous interaction between developers and users during system development, ensuring that the resulting system meets organizational requirements. Software quality testing was conducted based on eight ISO/IEC 25010 quality characteristics, namely Functional Suitability, Performance Efficiency, Compatibility, Usability, Reliability, Security, Maintainability, and Portability. The evaluation results indicate that the developed system achieved an overall score of 82.50%, which falls into the Very Good category, indicating that the system has met the expected software quality standards. Therefore, the proposed Document Management System is considered feasible to support document management activities and improve operational efficiency at PT Snapdev Digital Indonesia.